Fecal Microbial Transplantation and Its Potential Application in Cardiometabolic Syndrome - Leshem, Avner; Horesh, Nir; Elinav, Eran (Frontiers in Immunology, 2019)
Newly revealed links between inflammation, obesity and cardiometabolic syndrome have created opportunities to try previously unexplored therapeutic modalities in these common and life-risking disorders. One potential modulator of these complex disorders is the gut microbiome, which was described in recent years to be altered in patients suffering from features of cardiometabolic syndrome and to transmit cardiometabolic phenotypes upon transfer into germ-free mice. As a result, there is great interest in developing new modalities targeting the altered commensal bacteria as a means of treatment for cardiometabolic syndrome. Fecal microbiota transplantation (FMT) is one such modality in which a disease-associated microbiome is replaced by a healthy microbiome configuration. So far clinical use of FMT has been overwhelmingly successful in recurrent Clostridium difficile infection and is being extensively studied in other microbiome-associated pathologies such as cardiometabolic syndrome. This review will focus on the rationale, promises and challenges in FMT utilization in human disease. In particular, it will overview the role of the gut microbiota in cardiometabolic syndrome and the rationale, experience, and prospects of utilizing FMT treatment as a potential preventive and curative treatment of metabolic human disease.